EPIDEMIOLOGY OF RHYTHM DISORDERS IN CHILDREN - Ataeva Muhiba Sayfievna; Mardonov Umarzhon Yakub ugli (Scholar Express Journals, 2024)
Unlike the adult population, arrhythmias are less common in childhood. Only 5% of pediatric emergency hospitalizations are for symptomatic arrhythmias [3,6,9]. Most of these tend to be supraventricular tachyarrhythmias mediated by accessory pathways such as Wolff-Parkinson-White (WWS) syndrome, persistent junctional reentrant tachycardia (JRT) and Mahaheim tachycardia [1,2]. Supraventricular tachyarrhythmias mediated by non-accessory pathways, often observed in children, are nodal ectopic tachycardia (ET) and automatic ectopic atrial tachycardia (AET) [2] and occur mainly in the postoperative period after intracardiac repair for structural heart disease. Ventricular tachycardia (VT), although rare, occurs in the pediatric age group in association with hypertrophic cardiomyopathy (HCM), long QT syndrome (LQT), and Brugada syndrome. Occasionally, VT may also present symptomatically as incessant idiopathic infantile ventricular tachycardia, right ventricular outflow tract tachycardia, benign VT, catecholamine VT, idiopathic left ventricular tachycardia, and in patients after cardiac surgery.
Keywords: Ventricular tachycardia; hypertrophic cardiomyopathy; long QT syndrome